Balancing ties, democracy and freedom - Sotomayor Trelles, José Enrique (2019)
The present paper is framed in the general problem of the decision making process in cases of weighting or balancing ties. Although the theory of principles and weighing offered by Robert Alexy is taken into account in the formulation of the problem, in the proposal of solution –through three rules, applicable to the scenario of a weighing tie– we move away from the alexyan proposal. The rules offered here seek to be heuristics for solving cases of weighting ties.